WONDERSHARE QUIZ CREATOR BERBASIS ANDROID DALAM MATA PELAJARAN SOSIOLOGI KELAS XI IPS 2 MAN 1 MALANG - Fadlullah, Achmad Kholid (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2018)
The quality of education is determined by the integration between all learning components such as teachers, pre-facility facilities, curriculum, learning methods, learning media. The use of media is an effort to overcome learning problems. The media functions as an intermediary between educators and students in conveying information. To achieve this goal, the researchers developed a media that is an Android-based Wonder share Quiz Creator evaluation media. The purpose of the research is 1) To describe the specifications of the evaluation media for Wonder share Quiz Creator based on Android in Sociology subjects in XI IPS 2 MAN 1 Malang. 2) To develop an Android-based Wonder share Quiz Creator evaluation media in Sociology subjects in XI IPS 2 MAN 1 Malang. 3) To describe the results of the development of an Android-based Wonder share Quiz Creator media evaluation in Sociology subjects in XI IPS 2 MAN 1 Malang. The research method uses Research and Development (R D), referring to the model introduced by Borg and Gall. Techniques for collecting data through observation, tests, and questionnaires. Data analysis techniques used content analysis of learning and descriptive analysis. The results of this study indicate that: 1) Android-based Wonder share Quiz Creator evaluation media in sociology learning is an application containingâ€™s a variety of questions, random in nature, can be used online and offline. 2) Wonder share Quiz Creator media evaluation which was initially web-based in the computer was developed into an Android-based application 3) this development proved useful, interesting and valid in, based on 80% sociology material validator data, 73% design experts, and IPS 2 student responses 82.57%. The increase in learning outcomes pre-test and post-test from the results of t-test, T table is 3.23 1.68. This shows that the product developed has a high level of validity and high attractiveness, so it is suitable to be used in supporting the evaluation process.Keywords:Â wonder share quiz creator; android; social science